Ð’Ð»Ð¸ÑÐ½Ð¸Ðµ Ð»Ð¾ÐºÐ°Ð»ÑŒÐ½Ð¾Ð³Ð¾ ÐºÑ€Ð¸Ð¾Ð¿Ð¾Ð²Ñ€ÐµÐ¶Ð´ÐµÐ½Ð¸Ñ Ð¿ÐµÑ‡ÐµÐ½Ð¸ Ð½Ð° Ð¾ÑÐ½Ð¾Ð²Ð½Ñ‹Ðµ Ð±Ð¸Ð¾Ñ…Ð¸Ð¼Ð¸Ñ‡ÐµÑÐºÐ¸Ðµ Ð³ÐµÐ¿Ð°Ñ‚Ð¾Ð·Ð°Ð²Ð¸ÑÐ¸Ð¼Ñ‹Ðµ Ð¿Ð¾ÐºÐ°Ð·Ð°Ñ‚ÐµÐ»Ð¸ ÑÑ‹Ð²Ð¾Ñ€Ð¾Ñ‚ÐºÐ¸ ÐºÑ€Ð¾Ð²Ð¸ Ñƒ ÐºÑ€Ð¾Ð»Ð¸ÐºÐ¾Ð² - Sleta, I. V. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2002)
In blood serum of rabbits with normal liver and experimental liver cirrhosis we investigated the dynamics of the content of total protein, glucose, activity of alkaline phosphatase (APh), alanine- and aspartate aminotransferases (AlT and AsT), level of malone dialdehyde (MDA) after a local liver cryodestruction. Analysis of the dynamics of the mentioned indices allowed to conclude that local cryodestruction of normal liver has caused short-term and moderate impairments of its functional activity, and local cryoeffect on cirrhosis-changed liver significantly did not aggravate metabolic changes, characteristic for this disease.